DOSE SPARING OF INDUCTION DOSE OF PROPOFOL BY FENTANYL AND BUTORPHANOL: A COMPARISON BASED ON ENTROPY ANALYSIS - Dr Tejanand; Dr Lingaraju N; Dr R Suraj; Dr Sushrutha K P; Dr Rohith C S; Dr Chaitra N (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Entropy monitoring is a method of assessing anaesthetic depth. There is abundant literature on the analgesic properties of butorphanol and fentanyl and its efficacy as an adjuvant to epidural and intra-thecal local anaesthetics, but not on dose sparing of induction dose. Aim: The present study aims to compare the propofol requirement by fentanyl and butorphanol as pre-medication agent using entropy. Methodology: The study was conducted on inpatients of hospitals attached to our institute for a duration of 18 months. This is a Prospective Randomized control trial that that included two groups, namely GROUP B included patients on Butorphanol [20 µg/kg] and GROUP F included patients on Fentanyl [2 µg/kg]. Seventy patients were randomly selected for each group, thus a total of 140 patients were included in the study. Results: Response Entropy, State Entropy and Sedation score were comparable between group F and Group B without significant difference. The present study noted that Propofol requirement is comparable between group F and Group B without significant difference. Discussion: Major drawbacks of anesthetic induction with propofol are a greater degree of cardiorespiratory depression as compared with other hypnotic agents and inadequate attenuation of the hypertensive response to intubation. Conclusion: Butorphanol 20 μg/kg IV prior to the induction of anaesthesia reduces the induction dose of propofol, comparable to that of fentanyl 2 μg/kg IV and both the drugs are hemodynamic stable at induction and intubation.